“Hoje vou tratar de meus direitos”: liberdade precária, escravização ilegal, reescravização e o apelo à justiça, no Ceará Provincial (1830-1888) - Pedroza, Antônia Márcia Nogueira (2021)
The present study focuses on a society whose population of African-descendants has experienced different degrees of autonomy and precarious work relationships at different levels, or as an aggregate, subordinated to compulsory labor, or subjected to other arrangements that contributed to the instability of acquired rights preservation. Although the practice of enslaving free people existed long before 1830, legal disputes over illegal enslavement and re-enslavement were restricted to mechanisms of civil justice. From that year on, the first Criminal Code of a independent Brazil came into force, whose article 179 typified and criminalized the practice of reducing free people to slavery and established punishment of imprisonment and a fine for those who incurred this crime, making it possible for the enslavers of free people were held criminally responsible for this conduct, tried and eventually convicted and penalized. From the combination of quantitative and qualitative analysis of newspapers, civil and criminal cases and communication from the police head office, among other documents, we developed some hypotheses. One is that in the province of Ceará, in times of social crises caused by droughts, the boundaries between freedom and slavery became more blurred.Another is that the involvement, directly or indirectly, of administrative, police and Justice authorities, in cases of enslavement and re-enslavement, contributed to this practice dissemination, making it difficult to punish those responsible. We also defend the hypothesis that those free men, citizens with broad rights, who denounced enslavers of free people, who led fights in defense of the freedom of illegally enslaved people, did it so mainly when the enslaver was a political adversary or a personal disaffection. It is important to highlight that in this game that involved clientele networks, local political disputes and family intrigues, the enslaved and those who were under the threat of enslavement or re-enslavement knew which cards they could put on the table to gain access to Justice and obtain or maintain freedom.